IBD 7 A review of the factors affecting remission rates in a tertiary paediatric IBD cohort. (12th September 2022) - Saifuddin, Nisreen; Ocholi, Attah; Onyeador, Nkem; Paul, Thankam; Kapoor, Rajat; Reps, Nicholas
Abstract : Objectives/Introduction: Inflammatory bowel disease (IBD) is a chronic condition that is commonly diagnosed in the paediatric patient cohort. Due to its relapsing-remitting nature, it is important to tailor the treatment to each patient and achieveing good control as defined by treating to target which is a combination of symptom scores and objective markers including faecal calprotectin, blood tests, drug and metabolite levels, radiological and endoscopy assessment. The aims of this project are to identify the population of patients in remission in the IBD cohort and to identify the factors which affect this, particularly frequency of contact with IBD services. Methods: A retrospective review was carried out using the data available on electronic hospital records. The data included: patient demographics, type of treatment, most recent biochemical and radiological assessment results and hospital visits from paediatric IBD patients at an NHS hospital. All IBD subtypes were included. A Microsoft Excel spreadsheet was used to collect the data which was then reviewed by a senior consultant and subsequently analysed. Results: In total, 150 patients were included. 72.67% of these patients were either found to be in remission or had mild disease activity. Higher remission rates/mild disease activity was observed in patients who had seen a consultant and had biological tests done within 6 months (90.63%) as opposed to patients who had not (38.46%). More patients receiving combination treatment of either 5ASA/a biologic and an immunosuppressant were found to be in remission than patients receiving just one or none of these treatments. Conclusion: There appears to be a link between remission rates and local factors including frequent monitoring through biological and radiological assessments, consultation visits and the type of treatment. Frequent monitoring of IBD patients may lead to higher remission rates. This can be achieved via frequent consultation reviews to include up-to-date symptom scoring indices and biochemical and radiological assessments.